Review on performance of chromium-coated zirconium and its failure mechanisms - Li, Ziyi; Wang, Xiaomin; Chen, Huan; Zhang, Ruiqian; Wei, Tianguo; Yao, Lifu; Wang, Pengfei (Frontiers in Nuclear Engineering, 2023)
The conventional Zircaloy cladding may react with coolant in light water reactors and elicit severe accident at high temperature, which constraint the safe and efficient development of nuclear energy. To avoid the tragedy happened in Fukushima, the concept of Accident Tolerant Fuel (ATF) was developed around the globe to secure the steady operation for nuclear power plants. As a short-term solution, deposition of protective coatings upon the cladding tubes are proved to be effective. Among the coatings, Chromium is one of the most outstanding choices. This paper reviewed the recent study results about the performance and failure mechanisms of Cr-coated Zr cladding, including mechanical, irradiation, high-temperature oxidation tests etc. under normal and/or accident conditions. The experiments and tests collectively suggest that Cr coating possesses excellent comprehensive properties for integrity protection of claddings and provide a promising future of the commercial application in reactor cores. Finally, this review proposed ambiguities and questions needed to be analyzed and clarified in future works.